굴절조절내사시에 대한 5년간의 경과관찰결과 - 김동주; Dong Ju Kim; 전보영; Bo Young Chun; 권정윤; Jung Yoon Kwon (Daihan angwa haghoi jabji, 2007)
목적 : 굴절조절내사시의 임상양상 및 5년간 관찰결과를 알아보고자 하였다. 대상과 방법 : 5년 이상 경과관찰이 가능했던 굴절조절내사시 환자 43명을 대상으로 성별 및 연령별 분포, 내사시의 발생연령, 내원시기 등을 알아보고 경과관찰기간 동안의 사시각 및 원시도의 변화를 분석하였다. 결과 : 초진시 평균 굴절률은 4.42±3.27D였으며 최종검사시 평균 굴절률은 3.84±3.46D로 연간 0.12D의 감소를 보였다. 초진시 사시각은 평균 31.74±13.72PD 였으며 최종검사시 사시각은 평균 30.11±14.27PD 이었다. 43명 중 대상부전 증례는 3년 째 2명, 4년 째 1명에서 관찰되었다. 결론 : 굴절조절내사시에서는 원시의 정도 및 사시각이 시간 경과에 따라 감소할 수 있으므로, 장기간의 경과관찰과 이에 따른 적절한 조처가 필요하다. <한안지 48(2):315-320, 2007> Purpose: To evaluate the clinical characteristics of refractive accommodative esotropia followed up for 5 years. Methods: Forty-three subjects with refractive accommodative esotropia, who had been followed up for at least 5 years were included in this study. Age and sex distribution, age at onset and the interval between onset of esotropia and initial visit were evaluated. Changes of the angle of deviation and the amount of hyperopia during follow-up period were analyzed. Results: The initial amount of hyperopia of 4.42±3.27D was decreased to 3.84±3.46D by the last exam. The average rate of hyperopia decrease per year was 0.12 diopters. The average angles of deviation at the initial and final exam were 31.74±13.72PD and 30.11±14.27PD, respectively. Among the 43 subjects who participated in this study, decompensation occurred in 2 patients in the third year and 1 patient in the fourth year. Conclusions: There is a tendency for the amount of hyperopia to decrease over time. Further, deviation may deteriorate over time as well. Thus, long term follow-up management is necessary to control deviation in patients with refractive accommodative esotropia. J Korean Ophthalmol Soc 48(2):315-320, 2007